METHODS OF DEVELOPING TOLERANCE AMONG STUDENTS THROUGH THE “SHARQ TARONALARI” MUSIC FESTIVAL - Aziza Abdumannatova, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
In this article, pedagogical conditions and ways of methodological improvement for the development of tolerance in students through the "Sharq Taronalari" music festival are highlighted.